(untitled) (Journal of Informatics Education and Research, 2025)
Human resource marketing, or HRM, is the process of developing job openings while taking important aspects like job requirements, pay, and how best to convey employment offers. Financial salaries are only one type of compensation; other types of rewards for finished work are also included. Employee pay has garnered more attention in the last ten years, especially in relation to managerial positions and the changing Industry 4.0 environment. For managerial roles, well-written job descriptions are essential to luring qualified applicants. This essay seeks to investigate the connection between a few job search factors (job sources) and gender. To do this, a questionnaire survey on HRM practices in the Indian business environment was carried out. A return percentage of 35.44% was obtained from the 185 responses to the survey, which was directed at 522 people. Pearson’s chi-square test for independence and cluster analysis were used to analyze the data. Furthermore, for graphical representation, a Receiver Operating Characteristic (ROC) curve was utilized. According to the results, there is a considerable correlation between social networks and gender and both job servers and job sources. The ROC curve provided additional evidence of the relationship between employees’ work experience and predicted wage income.